Case study - apply a deep-learning algorithm to exomes detection with online resources - Maria da Conceição Proença; António Pedro Alves de Matos (Annals of Antivirals and Antiretrovirals - Peertechz Publications, 2021)
Exosomes are membrane vesicles that constitute a potential mode of intercellular communication. Although the scope of its role is still being discussed, the release of exosomes by tumor cells suggests their participation in pathological situations and its study will surely drive to new therapeutic and diagnostic strategies. It is therefore important to be able to localize and identify these kinds of particles in transmission electron microscopy images. This preliminary work shows how a recent deep-learning algorithm available online can be applied to exosomes images to localize all the instances of the objects of interest, in any scale and several backgrounds.